Utilization of Bluetooth Connections for Arduino Based Door Lock Security Tools - Hafdiarsya Saiyar (Jurnal Riset Informatika, 2020)
Home security is something that must be considered for every homeowner. Especially when you have to leave the house empty for work or even on vacation. You must be worried about thieves, lost jewelry, or the safety of other valuables. Therefore, the authors made a door lock security device by utilizing a Bluetooth connection with the Arduino Uno microcontroller. The research method used was direct observation of the selected object, namely the author's house, and conducting literature studies related to the Arduino Uno microcontroller. This door lock tool uses the Arduino Uno as a data processing center, because it is easy to use, and most importantly in the charging program, it does not require a download like a microcontroller in general. This Arduino Uno contains a special program that will give commands to the Servo Motor to open and open the door. Not only opening and opening doors, but this tool can also move the door without us holding or touching it but through a Smartphone. The purpose of this research is to produce a tool that can make it easier to manage or open doors using the Arduino via an Android smartphone using a Bluetooth connection.